Insanely great the life and times of Macintosh, the computer that changes everything - Levy, Steven 1951- (Viking, 1994)
Macintosh won over a fanatic cult audience with its friendly interface, its attention to aesthetic detail, and what could only be called its quirky personality. It invaded not only people's offices and homes, but their minds as well. The Mac also catapulted the computer industry into an unprecedented mix of technics, economics, and show biz. Eventually, the essence of Macintosh found its way to nearly all computers, and has fundamentally changed the way we deal with information